Instrumen Keterampilan Smash dalam Permainan Tenis Meja - Budi Indrawan; Iman Rubiana; Melya Nur Herliana (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2020)
The purpose of this study was to produce a product in the form of a smash skill instrument in a table tennis game, and to obtain the validity and reliability of a smash instrument for a table tennis game. This research uses the Sukmadinata research and development (R&D) method with a sample of table tennis athletes in the City of Tasikmalaya with cadet and junior age groups for a limited trial of 10 people and an extensive trial of 21 people. This test instrument was examined by expert judgment first, expert judgment for the test instrument was tested by table tennis experts and measurement test experts. The results of this study, the test instrument was declared valid and reliable seen from the results of calculations where the trial was limited the level of validity of the test was 0.70 and the reliability of the test was 0.87 while for the broadest trial the validity of the test was 0.47 and the reliability of the test was 0.59. In conclusion, the smash skills test instrument in a table tennis game can be used for the Tasikmalaya City area. Keywords: Instruments, Smash Skills, Table Tennis Games